2017
DOI: 10.1186/s12864-017-3706-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of ATP-binding cassette (ABC) transporters in the sweetpotato whitefly, Bemisia tabaci

Abstract: BackgroundABC transporter superfamily is one of the largest and ubiquitous groups of proteins. Because of their role in detoxification, insect ABC transporters have gained more attention in recent years. In this study, we annotated ABC transporters from a newly sequenced sweetpotato whitefly genome. Bemisia tabaci Q biotype is an emerging global invasive species that has caused extensive damages to field crops as well as ornamental plants.ResultsA total of 55 ABC transporters containing all eight described sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 108 publications
2
59
0
1
Order By: Relevance
“…Forty-five and 50 putative ABC and CCE genes were annotated in the F. occidentalis genome, respectively ( Additional file 2: Table S15 and S16 ). The number of F. occidentalis ABC genes is on the lower side among those reported for other insect species ( Additional file 1: Section 7.2, Table S7.3 , [87, 88]), including Bemisia tabaci of the Hemiptera, the sister-group of the Thysanoptera [89]. Nevertheless, we did identify a lineage-specific expansion of ABCH genes within the F. occidentalis genome ( Additional file 1: Section 7.2, Figure S7.6 ).…”
Section: Plant Feedingmentioning
confidence: 95%
“…Forty-five and 50 putative ABC and CCE genes were annotated in the F. occidentalis genome, respectively ( Additional file 2: Table S15 and S16 ). The number of F. occidentalis ABC genes is on the lower side among those reported for other insect species ( Additional file 1: Section 7.2, Table S7.3 , [87, 88]), including Bemisia tabaci of the Hemiptera, the sister-group of the Thysanoptera [89]. Nevertheless, we did identify a lineage-specific expansion of ABCH genes within the F. occidentalis genome ( Additional file 1: Section 7.2, Figure S7.6 ).…”
Section: Plant Feedingmentioning
confidence: 95%
“…In recent years, ABC transporters have become a major focus for research in arthropods. This is in part due to their overall role in xenobiotic transport and insecticide resistance [25,[47][48][49][50], but more specifically, due to their suspected role in susceptibility to Bt toxins [38,51,52]. For example, Gahan et al [53] reported genetic linkage of Heliothis virescens HvABCC2 with resistance to Cry1Ac, while changes in the structure, splicing, or expression level of ABCC2 orthologs were later associated with Cry1Ac resistance in Helicoverpa armigera [54], Bombyx mori [55], and Spodoptera exigua [56].…”
Section: Discussionmentioning
confidence: 99%
“…RNA was quantified using a NanoDrop 2000 (Thermo Scientific, Wilmington, DE, USA), and purity was checked on 1% agarose gels. RNA‐seq libraries were constructed; the reads per kilobase per million mapped read values were calculated as previously described (He et al ., ; Tian et al ., ).…”
Section: Methodsmentioning
confidence: 97%
“…The candidate B. tabaci SDGs were confirmed using the blastx algorithm against the nonredundant protein sequence (NR) database of GenBank. The exon–intron boundary and start–stop codons of each SDG were identified from the genome and transcriptome dataset assembled from SRP064690 (He et al ., ; Tian et al ., ; Yang et al ., ). The deduced protein domains were determined using the NCBI Conserved Domain Search Service.…”
Section: Methodsmentioning
confidence: 99%